1975
DOI: 10.1159/000466852
|View full text |Cite
|
Sign up to set email alerts
|

Assay of α-TV-Acetylgalactosaminyltransferases in Human Sera

Abstract: The study of the α-N-acetylgalactosaminyltransferase in the sera of 19 individuals belonging to the rare A(m) blood group makes it possible to confirm the heterogeneity of this phenotype established on genetical and immunological criteria. Two groups of subjects, A(m) and A(y), can be distinguished. For the individuals of the first group, named A(m), 15 samples (7 families) have been studied, the phenotype is inherited as an allele at the ABO locus. 14 of these subjects, have an α-N-acetylgalactosaminyltransfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
4
6
0
Order By: Relevance
“…(4) Absence of the A transferase activity in the sera of members of the L. family with postulated A, phenotypes is in agreement with earlier data of Curtron et al [8].…”
Section: Discussionsupporting
confidence: 92%
“…(4) Absence of the A transferase activity in the sera of members of the L. family with postulated A, phenotypes is in agreement with earlier data of Curtron et al [8].…”
Section: Discussionsupporting
confidence: 92%
“…The H transferase activities in their serums were within the normal range. (4) Absence of the A transferase activity in the sera of members of the L. family with postulated Ay phenotypes is in agreement with earlier data of Cartron et al [8], Subsequently, however, employing prolonged incubation times, Cartron [9] reported very weak A transferase activ ities ranging from '/so to V200 of control samples in 4 unrelated Ai individuals. Initially, we have also reported very weak A transferase activities in the sera of the mem bers of the L. family with weak A phenotypes [10].…”
Section: Discussionsupporting
confidence: 90%
“…Enzyme assays in human sera: A and B enzyme assays have been described [28,29]. H enzyme assays were carried out in total vol.…”
Section: Northholland Publishing Company -Amsterdammentioning
confidence: 99%